Дослідження ефективності бездротових протоколів передачі даних у медичних IoT -системах - Склярова, В. А. (ХНУРЕ, 2025)
The models of efficiency of wireless data transmission protocols in IoT systems for monitoring human health indicators were studied. During the study, a comparison of the operation of popular data transmission protocols was created, taking into account the specifics of application in medical IoT systems. The result is the selection of the optimal protocol for the developed system.
Keywords: медична IoT -система; бездротовий протокол